Clove Oil Extraction by Steam Distillation and Utilization of Clove Buds Waste as Potential Candidate for Eco-Friendly Packaging (Universitas Negeri Semarang, 2020)
As a tropical country which has abundant of spices, Indonesia is challenged to increase the economic values of spices commodity in raw material form (wet or dry). One way to raise the economic values of these commodities is by modifying into its derivatives. Clove is one of spices commodity which can be processed furthermore into an essential oil. By transforming clove from raw material to essential oil, the economic value increases from 2 to 20 times per kilogram.Â In this present research, the extraction time of clove oil using steam hydro distillation is reported. The distillation procedure was conducted in various times, that was in 3, 4, 5, and 6 hours. Furthermore, the clove oil sample that obtained from optimum extraction time was characterized using FTIR and GCMS. Then the result was compared to the commercial clove oil (100 % of purity). In support of sustainability process, then the clove buds waste from steam distillation were challenging to be one of eco-friendly packaging candidates. Two compositions of waste and additional material have been investigated in this study. It found that the best composition was composed of clove buds waste powder: recycled paper (7:3). During the casting process, some additives material was added such as tapioca (20%) and chitosan (1 %) in acid solution in order to improve its mechanical properties. Furthermore, thermal degradability of the eco-friendly packaging was studied. It was started to degrade at 286.58oC. According to this research, the cloves budsâ€™ cardboard was quite potential to be developed as commercial eco-friendly packaging.